Solitary colonic metastasis from primary lung adenocarcinoma first presenting as intestinal obstruction: A case report. Issue 3 (January 2019) - Choi, Sang-ji; Hong, Seong Kweon; Chae, Gibong; Ryu, Young-Joon; Park, Sung-Bae; Kim, Yang Hee; Moon, Suk-Bae; Kim, Song-Yi; Kim, Hwansoo
Abstract: Rationale: The brain, liver, adrenal glands, and bone are the most common sites of metastatic disease in patients with lung cancer. Symptomatic gastrointestinal metastases are rare. In the present report, we describe a rare case of a patient with intestinal obstruction due to solitary colonic metastasis from primary lung adenocarcinoma, wherein the intestinal obstruction was the first symptom of lung cancer. Patient concerns: A 74-year-old man was admitted to the emergency room with abdominal pain and vomiting, and abdominal computed tomography (CT) indicated obstruction of the ascending colon due to a huge mass. Diagnosis: The ascending colon cancer was found to be a metastatic adenocarcinoma based on the results of the pathology report. Chest CT and positron emission tomography-CT were performed to identify the cancer origin site. Moreover, immunohistochemical staining of the tissue specimen for thyroid transcription factor 1, cytokeratin 7 (CK7), and CK20 and CT-guided gun biopsy of the lung mass confirmed the presence of an adenocarcinoma that originated from the lung. Intervention: Right hemicolectomy was performed as the primary treatment. Outcomes: The patient recovered without any problems due to the surgery itself. However, malignant pleural effusion deteriorated, and no additional palliative chemotherapy was performed. Lessons: Patients with malignant bowel obstruction along with lung infiltration should be suspected of not only colon cancer with lung metastasis, but also lung cancer with colon metastasis.